2, 3, 3, 3‐Tetrafluorpropen [MAK Value Documentation in German language, 2019]. Issue 1 (30th January 2019) - Hartwig, A.; ,
Abstract: The German Commission for the Investigation of Health Hazards of Chemical Compounds in the Work Area has re‐evaluated the maximum concentration at the workplace (MAK value) of 2, 3, 3, 3‐tetrafluoropropene [754‐12‐1 ]. As the blood:air partition coefficient of 2, 3, 3, 3‐tetrafluoropropene is < 5, the increased respiratory volume at the workplace (see List of MAK and BAT Values, Sections I b and I c) does not have to be taken into account for the derivation of the MAK value. Moreover, the extrapolation of 6‐hour exposure in the animal experiment to 8‐hour exposure at the workplace does not need to be applied because the effect is much more dependent on the concentration than on time. The MAK value for 2, 3, 3, 3‐tetrafluoropropene of 200 ml/m 3 can therefore be retained.